Optimizing Class Evaluation as A Basis for Improving the Quality of Teacher Teaching - Suhartini Suhartini; Sugeng Sugeng (Global Education Journal, 2025)
This study aims to analyze classroom evaluation as an instrument for improving teaching quality through a literature review of scientific journals, academic books, and policy documents. The study was conducted to address the issue of inequality in teaching quality influenced by evaluation practices that still focus on student outcomes, rather than the learning process. The results of the review indicate that classroom evaluation plays a crucial role in strengthening teacher professionalism through reflective practice, classroom observation, and providing meaningful feedback. Both global and national literature confirm that systematic, dialogic, and data-driven evaluation can improve instructional effectiveness and foster a culture of reflection in teaching practice. Other findings reveal structural and cultural barriers to the implementation of classroom evaluation in Indonesia, such as administrative constraints, teacher workloads, and evaluators' limited capacity to provide constructive feedback. These conditions often lead to evaluation being perceived as a means of control, rather than a means of professional development. This study concludes that repositioning classroom evaluation as a collaborative process that supports continuous improvement in teaching quality is crucial. Recommendations include strengthening evaluator competencies, developing contextual evaluation guidelines, and conducting field research to delve deeper into teachers' experiences.